ANALISIS KELAS SOSIAL DALAM MEMBACA IKLAN - Arizal Mutahir (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
Many studies on advertising in Indonesia have been conducted. The discussions are mostly about the influence of advertising on consumers. However, such studies often slip into a deterministic understanding. Actions are understood as behaviors merely influenced by external factors. The study of advertising deals with the relationship between the subject's intentions, actions, and the meanings contained in the advertisement. Thus, it not only discusses the influence of advertising on consumption behavior, but also requires a study of representation in advertising. Unfortunately, some studies of advertising representation have not touched the theme of the representation of social classes, as if advertisements don't talk about social classes explicitly. The absence of social class analysis in advertisement study tends to disguise the actual conditions of the society. Using the method of semiotic analysis to read advertisements on television as the subject of the study, this paper aims to show that images of social class are still present in advertisements. This paper finds that social class images in advertisements are stereotyped. The lower social class is described as a social class that is dominated and is doing a class-passing. Based on the findings, this paper argues that the analysis of social classes is still required to examine any forms of popular culture such as advertising and, at the same time, can show the actual conditions of social classes in the society.